Characterization of the expression of HTm4 (MS4A3), a cell cycle regulator, in human peripheral blood cells and normal and malignant tissues - Kutok, Jeffery L (Blackwell Publishing Ltd, 2011)
HTm4 (MS4A3) is a member of a family of four-transmembrane proteins designated MS4A. MS4A proteins fulfil diverse functions, acting as cell surface signalling molecules and intracellular adapter proteins. Early reports demonstrated that HTm4 is largely restricted to the haematopoietic lineage, and is involved in cell cycle control, via a regulatory interaction with the kinase-associated phosphatase, cyclin A and cyclin-dependent kinase 2 (CDK2). Here we describe the expression pattern of HTm4 in peripheral blood cells using gene expression microarray technology, and in normal foetal and adult human tissues, as well as adult human cancers, using tissue microarray technology. Using oligonucleotide microarrays to evaluate HTm4 mRNA, all peripheral blood cell types demonstrated very low levels of HTm4 expression; however, HTm4 expression was greatest in basophils compared to eosinophils, which showed lower levels of HTm4 expression. Very weak HTm4 expression is found in monocytes, granulocytes and B cells, but not in T cells, by lineage specific haematopoietic cell flow cytometry analysis. Interestingly, phytohaemagglutinin stimulation increases HTm4 protein expression in peripheral blood CD4-T-lymphocytes over nearly undetectable baseline levels. Western blotting and immunohistochemical studies show strong HTm4 expression in the developing haematopoietic cells of human foetal liver. Immunohistochemical studies on normal tissue microarrays confirmed HTm4 expression in a subset of leucocytes in nodal, splenic tissues and thymic tissue, and weak staining in small numbers of cell types in non-haematopoietic tissues. Human foetal brain specimens from 19 to 31 gestational weeks showed that the strongest-staining cells are ventricular zone cells and the earliest-born, earliest-differentiating ‘pioneer’ neurons in the cortical plate, Cajal-Retzius and, to a lesser extent, subplate-like neurons. Malignant tissue microarray analysis showed HTm4 expression in a wide variety of adenocarcinomas, including breast, prostate and ovarian. These findings warrant the further study of the role of HTm4 in the cell cycle of both haematopoietic and tumour cells.